Influence of external actors on national information and communications technology policy formulation in developing countries: case of Malawi - Kunyenje, Gregory (Department of Information Systems, 2019)
Problem statement – A national Information and Communication Technology (ICT) policy is important towards attainment of socio-economic development of a country. Like other public policies, the formulation and implementation of national ICT policy is a government’s responsibility. In developing countries, the formulation of national ICT policies is mostly influenced by actors who are external to a country. The external influence may affect the soundness of the resulting public ICT policy during a policy making activity and in turn affect the needs of society in a country. There is need, therefore, for research focusing on the effects of the external influence in the formulation of a public ICT policy in Africa. Currently, there is dearth of research in this area. Purpose of the research – This study analysed how the influence of external actors affects the formulation of national ICT policies in Africa by: (1) investigating the engagement between external and local actors, (2) identifying categories of influence of external actors and (3) exploring the link between country context and influence of external actors. A study analysing how the influence of external actors affects the formulation of national ICT policy in developing countries may contribute towards the effectiveness of the public ICT policy that may lead to better management of interaction between internal and external actors. Design/methodology/approach – The study adopted a critical research approach and drew on Bourdieu’s Theory of Practice as a theoretical lens to examine how the influence of external actors affects the formulation of national ICT policies in developing countries. This was a qualitative study, which used Malawi as a case study. Primary data were collected through semi-structured interviews with 18 respondents who took part in the formulation of the national ICT policy in Malawi. Secondary data for the research were sourced from policy documents and reports from Malawi and from other African countries. Data analysis in the Malawi case applied thematic analysis while content analysis was used for the five comparative case countries. Findings – The study finds that there is little engagement between local and external actors during public ICT policy formulation. The findings also show that the influence of external actors is likely to affect formulation of public ICT policies in poor countries. The external actors use different forms of capital and consequently play roles such as setting a policy agenda and setting policy priorities for a developing country which is contrary to the tradition of external actors providing funding and technical support. Further, the study finds that when external actors set the policy agenda for a country then local actors may adopt content prescribed by the external actors in the resulting policy. Originality/contributions – This thesis makes contributions to knowledge: (1) the use of Bourdieu’s Theory of Practice to explore and explain how the influence of external actors affects the formulation of a national ICT policy; (2) the body of knowledge on national ICT policy formulation research; and (3) the identification of appropriate theories that can inform future research in the formulation of a national ICT policy in Africa